The Influence of Leadership, Non-Physical Work Environment and Job Satisfaction on Employee Turnover Intention at the “SiCepat Ekspres” Expedition, Ponorogo Branch - Quliyawan, Ariyandi; Hartono, Sri; Wijianto, Wijianto (PT. Anagata Sembagi Education, 2025)
This study aims to determine the effect of leadership, nonficical workmanship and work statistics for turnover intention of employees in the Ponorogo Branch